Retrospective Preliminary Assessment of Routine Follow-Up Low-Field Magnetic Resonance Imaging in Dogs Presumptively Diagnosed With Discospondylitis - de Freitas, Maria Ines; Vettorato, Enzo; Scarpante, Elena; Cherubini, Giunio Bruto; Caine, Abby (Frontiers in Veterinary Science, 2022)
Background: The usefulness of routine follow-up Magnetic Resonance Imaging (MRI-2) in asymptomatic dogs treated for discospondylitis is unknown. Methods: This cross-sectional retrospective study investigated the features of MRI-2 in a heterogeneous group of dogs treated for discospondylitis, and if these were associated with the presence or absence of clinical signs. After comparing initial MRI (MRI-1) and MRI-2, an observer, blinded to the dog’s clinical signs, described the MRI-2 findings. The study population was then divided into symptomatic or asymptomatic at the time of MRI-2. Two separate observers subjectively classified the discospondylitis as active or inactive. Repeatability and interobserver agreement were evaluated. Results: A total of 25 dogs were included. At the time of MRI-2 16 (64%) dogs were asymptomatic and 9 (36%) were symptomatic. Based on MRI-2, 20 (80%) and 18 (72%) out of 25 dogs were considered to have active discospondylitis by the first and second observers, respectively. Interobserver agreement was moderate. No MRI-2 features were associated with the clinical status. The subjective classification of inactive discospondylitis was significantly associated with asymptomatic clinical status, but the classification of active discospondylitis was evenly distributed between groups. Conclusion: This study did not identify a meaningful association between the clinical status of dogs treated for presumptive discospondylitis and MRI-2 results. There were no specific MRI-2 features which were associated with the clinical status.